In a Class of Their Own – RXFP1 and RXFP2 are Unique Members of the LGR Family - Petrie, Emma J.; Lagaida, Samantha; Sethi, Ashish; Bathgate, Ross A. D.; Gooley, Paul R. (Frontiers in Endocrinology, 2015)
The leucine-rich repeat-containing G protein-coupled receptors (LGRs) family consists of three groups: type A, B and C and all contain a large extracellular domain made up of the structural motif – the leucine rich repeat. In the LGRs the extracellular domain binds the hormone or ligand, usually through the leucine rich repeats, that ultimately results in activation and signalling. Structures are available for the extracellular domain of type A and B LGRs, but not the type C LGRs. This review discusses the structural features of leucine rich repeat proteins, and describes the known structures of the type A and B LGRs and predictions that can be made for the type C LGRs. The mechanism of activation of the LGRs is discussed with a focus on the role of the LDLa (low density lipoprotein class A) module, a unique feature of the type C LGRs. While the LDLa module is essential for activation of the type C LGRs, the molecular mechanism for this process is unknown. Experimental data for the potential interactions of the type C LGR ligands with the leucine rich repeat domain, the transmembrane domain and the LDLa module are summarized.